Interpersonal Leadership in Healthcare Teams: a Systematic Review on Strengthening Collaboration and Performance - Annisa Clara Salsabila; Alif Fatimatuz Zahro; Aurel Artamevia (Jurnal Ners, 2026)
Background: Leadership is vital in shaping effective teamwork by strengthening interpersonal dynamics within healthcare. Strong leadership enhances communication, trust, empathy, and psychological safety, key factors for collaboration in complex, multidisciplinary systems. Methods: A systematic literature review was conducted following PRISMA 2020 guidelines. Articles were retrieved from PubMed and SCOPUS using the keywords “leadership,” “teamwork,” “interprofessional,” and “healthcare.” Studies published between 2020 and 2024 were included. Of 43 initially identified articles, 9 met the eligibility criteria for full review. Results: Transformational, inclusive, adaptive, and trauma-informed leadership styles were found to significantly enhance teamwork. Core behaviors such as empathy, active listening, role clarity, and emotional support were consistently associated with higher team engagement, job satisfaction, and improved patient outcomes. Contextual adaptability was crucial for sustaining collaboration. Conclusion: Effective leadership fosters interpersonal collaboration and strengthens team performance. Leadership development should prioritize relational competence and emotional intelligence. Keywords: Leadership; interprofessional collaboration; psychological safety; team performance; teamwork